2005
DOI: 10.3354/ame041153
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect on a nutrient-limited phytoplankton species

Abstract: For aquatic systems, studies on allelopathic interactions among phytoplankton have increased over recent years, with the main focus on the role of the donor organism. In this study, we report on the response of a target organism to allelochemicals and whether this response was affected by stress conditions (nutrient limitation). We exposed the diatom Thalassiosira weissflogii, grown under different nitrogen (N) and phosphorus (P) conditions (NP, -N, or -P), to single or daily additions of a cell-free filtrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 32 publications
2
48
0
1
Order By: Relevance
“…Further, the annual cover crops might have been less effective, particularly against the perennial exotic species. Also, we might have observed more evidence of allelopathy, since allelopathic plants may produce more phytotoxins and target species may be more sensitive to allelochemicals when resources are scarce (Graneli and Johansson 2003;Fistarol et al 2005).…”
Section: Methodological Limitationsmentioning
confidence: 92%
“…Further, the annual cover crops might have been less effective, particularly against the perennial exotic species. Also, we might have observed more evidence of allelopathy, since allelopathic plants may produce more phytotoxins and target species may be more sensitive to allelochemicals when resources are scarce (Graneli and Johansson 2003;Fistarol et al 2005).…”
Section: Methodological Limitationsmentioning
confidence: 92%
“…The value of microalgae as food source depends on some characteristics such as cell size and biochemical composition (Becker, 2004). In particular, the diatom Thalassiosira weissflogii (Fryxell & Hasle, 1977) has been widely used as live feed in aquaculture; however information related to its chemical composition is still scarce (Li, 1979;Emmerson, 1980;Fistarol et al, 2005). Environmental factors have been reported to influence the chemical composition of microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that allelopathic interactions between phytoplankton are an important aspect of competition. For example, cell-free filtrate from the prymnesiophyte Prymnesium parvum inhibits the growth of the diatom Thalassiosira weissflogii and the nutrient status of the diatom affects its response to the filtrate (Fistarol et al, 2005). The most common effects of allelochemicals are cell lysis and growth inhibition (Legrand et al, 2003).…”
Section: Allelochemicalsmentioning
confidence: 99%